2017
DOI: 10.1039/c6ra27642c
|View full text |Cite|
|
Sign up to set email alerts
|

Adhesive-free adhesion between polytetrafluoroethylene (PTFE) and isobutylene–isoprene rubber (IIR) via heat-assisted plasma treatment

Abstract: A polytetrafluoroethylene (PTFE) surface was modified using atmospheric pressure plasma treatment under heating (heat-assisted plasma treatment) to promote its direct adhesion to isobutylene–isoprene rubber (IIR) without any adhesives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 36 publications
0
31
0
Order By: Relevance
“…A study by Guruvenket et al (2004) showed that the treatment of polymer surfaces by an Ar plasma jet, led to a hydrophilic surface which is attributed to the well known CASING process. Ohkubo et al have recently showed the CC crosslink formation on the PTFE surface via heat‐assisted helium plasma treatment, resulting from a heat‐assisted atmospheric pressure microwave plasma torch. The latter drastically improved the adhesion property of PTFE with respect to isobutylene–isoprene rubber and prolonged the lifetime of the surface modification.…”
Section: Resultsmentioning
confidence: 99%
“…A study by Guruvenket et al (2004) showed that the treatment of polymer surfaces by an Ar plasma jet, led to a hydrophilic surface which is attributed to the well known CASING process. Ohkubo et al have recently showed the CC crosslink formation on the PTFE surface via heat‐assisted helium plasma treatment, resulting from a heat‐assisted atmospheric pressure microwave plasma torch. The latter drastically improved the adhesion property of PTFE with respect to isobutylene–isoprene rubber and prolonged the lifetime of the surface modification.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that plasma treatment at low temperature (below 100 C) has a little effect on the adhesion property of PTFE and HAP treatment (above 200 C) has a signicant effect on its adhesion property. [20][21][22] Thus, the surface of each PTFE sheet was modied via HAP treatment according to the protocol reported previously. 21 However, in this study, the air concentration was controlled by the base pressure (as shown in ESI-1 †) during the HAP treatment.…”
Section: Heat-assisted Plasma (Hap) Treatment Methodsmentioning
confidence: 99%
“…HAP treatment involves applying heat to the PTFE surface by plasma treatment to induce surface hardening and introduce oxygen-containing functional groups. 20,21 HAP treatment has been shown to effectively improve both the indirect adhesion using an adhesive and direct adhesion (without an adhesive) of PTFE to other materials. 22 However, the HAP treatment in the previous studies was a leaf-type process: the pressure in the chamber was reduced to below 10 Pa using a rotary vacuum pump, and helium (He) gas was subsequently owed into the chamber until it reached atmospheric pressure (101 300 Pa).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, novel approach with a heat-assisted plasma surface modification at atmospheric pressure has been reported to demonstrate the improved adhesion between PTFE and rubbers [16]. However, PTFE surface was heated up to about 250°C by plasma irradiation and external heater, which is close to the maximum operating temperature of PTFE at 260°C.…”
Section: Introductionmentioning
confidence: 99%